Experiences In Comprehensive Vector Control In Indonesia - Nalim, Sustriayu (Media Penelitian dan Pengembangan Kesehatan, 1996)
The vector control program has been implemented in Indonesia for many years, however, vector-borne diseases are presently still a problem in Indonesia. Past activities for vector control implemented indoor residual spraying and larviciding only. Vector control problems occur through many causes and this has complicated past control programs. Presently, these complicated causes are surveyed thoroughly and analyzed as a whole and a holistic approach implemented. Comprehensive vector control is determined to solve the vector control problem. In 1991, a study was conducted to introduce the Malaria Surveillance Program in Indonesia. This program uses the comprehensive and integrated approach for malaria control in general, and vector control in particular. This paper describes the vector control program in general and how comprehensive vector control is integrated into the system. It also describes the experiences obtained in Indonesia and its impact on malaria in various places in Indonesia.